PENENTUAN PERIODE KRISIS EKONOMI DAN IDENTIFIKASI VARIABEL LEADING DI INDONESIA, 1990 â 2013 - , M. Indra Maulana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper will investigate the period of economic crisis in Indonesia and its leading variables. To determine period of economic crisis, this paper used currency crisis as a proxy for the crisis. Meanwhile, to determine leading variables, this paper used 35 economic variables. Using monthly data for January 1990-December 2013, this paper found that most of the crises periods are clustered on Asian Crisis 1997-98. This paper also found that only 13 variables are identified as the leading, which are consisting of exchange rate, banking, and stock market.